Scientific investigation of the lacquered wooden coffin of Xiang Fei excavated from Eastern Royal Tombs of the Qing Dynasty. (10th August 2017) - Hao, Xinying; Wu, Hao; Zhao, Yang; Tong, Tong; Li, Xiaoyuan; Yang, Cui; Tang, Yun; Shen, Xinyu; Liu, Shinian; Tong, Hua
Abstract : The composition, structure, and lacquering craft used to manufacture the coffin of Xiang Fei were analyzed using multiple analytical methods. Abstract : This work presents the results of an investigation into the lacquered wooden coffin of Xiang Fei excavated from Eastern Royal Tombs of the Qing Dynasty in China (Qing States, 1644–1912 AD). The composition, structure and lacquering craft of the coffin sample were analyzed using stereoscopic microscopy, SEM-EDS, XRD, FT-IR, RS, and Py-GC/MS methods. The results showed that, from inside to outside, the coffin sample consisted of a wooden body layer, lacquer ash layer (including four stucco layers and three fiber layers with alternating coverage), ground lacquer layer, and lacquer film pigment layer, which indicated that it had been lacquered several times. Several distinguished lacquering crafts were identified, including "anti-corrosion treatment" (treating the wooden body with cinnabar), "wan lacquering" (pasting fabric to the stucco then pasting stucco to the fabric repeatedly with lacquer), "grinding and polishing", "Jin Jiao" (mixture for joining the pigment layer to the preparation layer) and "carved lacquer". These processes can improve the stability and mechanical strength of the coffin body. The chemical composition of the film coating was analyzed by FT-IR, RS, and Py-GC/MS. The results show that the film coating consisted of orpiment, cinnabar, lacquer sap, SiO2, drying oil, animal gum, and proteinaceous materials. Furthermore, the presence of the three distinctive catechols, and other catechol and phenol profiles based on mass peaks at m / z 123 and m / z 108 ions clearly indicated that the species of lacquer tree was Rhus vernicifera .